Seguimiento de Graduados de las Residencias del Hospital Italiano - Eymann, Alfredo; Carrió, Silvia; Durante, Eduardo; Barros, María Victoria; Figari , Marcelo; Blanco, Osvaldo (Revista del Hospital Italiano de Buenos Aires, 2009)
.